Pediatric trauma triage: A Pediatric Trauma Society Research Committee systematic review. Issue 4 (October 2020) - Mora, Maria Carmen; Veras, Laura; Burke, Rita V.; Cassidy, Laura D.; Christopherson, Nathan; Cunningham, Aaron; Jafri, Mubeen; Marion, Erica; Lidsky, Karen; Yanchar, Natalie; Wu, Lin; Gosain, Ankush
Abstract : BACKGROUND: Significant variability exists in the triage of injured children with most systems using mechanism of injury and/or physiologic criteria. It is not well established if existing triage criteria predict the need for intervention or impact morbidity and mortality. This study evaluated existing evidence for pediatric trauma triage. Questions defined a priori were as follows: (1) Do prehospital trauma triage criteria reduce mortality? (2) Do prehospital trauma scoring systems predict outcomes? (3) Do trauma center activation criteria predict outcomes? (4) Do trauma center activation criteria predict need for procedural or operative interventions? (5) Do trauma bay pediatric trauma scoring systems predict outcomes? (6) What secondary triage criteria for transfer of children exist? METHODS: A structured, systematic review was conducted, and multiple databases were queried using search terms related to pediatric trauma triage. The literature search was limited to January 1990 to August 2019. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology was applied with the methodological index for nonrandomized studies tool used to assess the quality of included studies. Qualitative analysis was performed. RESULTS: A total of 1, 752 articles were screened, and 38 were included in the qualitative analysis. Twelve articles addressed questions 1 and 2, 21 articles addressed question 3 to 5, and five articles addressed question 6. Existing literature suggest that prehospital triage criteria or scoring systems do not predict or reduce mortality, although selected physiologic parameters may. In contrast, hospital trauma activation criteria can predict the need for procedures or surgical intervention and identify patients with higher mortality; again, physiologic signs are more predictive than mechanism of injury. Currently, no standardized secondary triage/transfer protocols exist. CONCLUSION: Evidence supporting the utility of prehospital triage criteria for injured children is insufficient, while physiology-based trauma system activation criteria do appropriately stratify injured children. The absence of strong evidence supports the need for further prehospital and secondary transfer triage-related research. LEVEL OF EVIDENCE: Systematic review study, level II. Abstract : Supplemental digital content is available in the text.